Preparation method and application of nickel-based aerogel catalyst
By uniformly dispersing nickel nanoparticles in the SiO2 aerogel support and using supercritical drying and calcining treatment, the problem of carbon deposits and sintering of nickel-based catalysts at high temperatures is solved, and higher stability and catalytic activity are achieved, and the efficiency of methane dry reforming reaction is improved.
Patent Information
- Application Number
- CN202411818781.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Existing nickel-based catalysts are prone to carbon deposits and sintering at high temperatures, resulting in catalyst deactivation, limiting their application in methane dry reforming reactions.
SiO2 aerogel is used as a support to uniformly disperse nickel nanoparticles in the mesoporous pores of the aerogel, and the aggregation of active nanoparticles is suppressed by the domain-limiting effect of the channel wall, and the stability of the catalyst is improved by supercritical drying and calcining treatment.
The formation of carbon deposits is significantly reduced, the stability and catalytic activity of the catalyst are improved, the utilization rate of light energy is enhanced, and the efficiency of methane dry reforming reaction is improved.
Smart Images

Figure BDA0005182566130000041 
Figure BDA0005182566130000051 
Figure BDA0005182566130000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy materials, and specifically relates to a nickel-based aerogel catalyst and a preparation method and application thereof. Background Art
[0002] The pace of global industrialization is accelerating. With the widespread use of fossil fuels such as coal, oil, and natural gas, the greenhouse effect is becoming more serious. Carbon dioxide and methane are the two greenhouse gases with the highest global emissions, accounting for 79% and 11% of the total greenhouse gas emissions respectively. Among them, the greenhouse effect of methane is 22 times that of carbon dioxide, and its emissions are increasing year by year, which makes the development of effective energy-saving and emission reduction technologies particularly important.
[0003] The methane dry reforming reaction can simultaneously convert two greenhouse gases, methane and carbon dioxide, and produce a 1:1 synthesis gas of H2 and CO, which can be directly used as a raw material for Fischer-Tropsch synthesis and hydroxyl synthesis, so it has important research value. However, since CO2 and CH4 are both very stable molecules, the CH bond and C=O have extremely high dissociation energies of up to 439.3 and 750.0 kJ / mol respectively, so in thermal catalysis, high temperatures of more than 800°C are often required to promote the reaction, which not only increases energy consumption, but also easily leads to catalyst sintering and deactivation due to excessively high temperatures. As the advantages of photocatalysis gradually emerge, studies have found that the introduction of light into the methane dry reforming reaction can reduce its reaction temperature, avoid catalyst sintering, improve its stability, and inhibit the generation of carbon deposition and reverse water-coal reaction to a certain extent, thereby improving catalytic selectivity.
[0004] Currently, supported metal catalysts are the most widely used choice for the research of methane dry reforming catalysts. Precious metals such as Au, Pt, Rh, Ru, and Ir exhibit excellent catalytic performance under light conditions due to their good local surface plasmon effect, but their high cost limits their practical industrial applications. Nickel-based catalysts have attracted much attention due to their low price and high efficiency. However, nickel-based catalysts are prone to carbon deposition and sintering at high temperatures, resulting in catalyst deactivation. Therefore, the current research focus is on how to effectively reduce the instability of nickel-based catalysts during the reaction process.
[0005] Aerogel, as a macroscopic porous material, has low thermal conductivity, large specific surface area and high porosity, and is widely used in the fields of adsorption, catalysis, energy and environment. Loading the catalytic material onto the aerogel carrier can not only retain its rich pore structure and large specific surface area, but also improve the dispersibility of the catalytic components and accelerate the transfer and adsorption of reactants to the active sites. This design fully combines the functions of the catalyst and the advantages of aerogel. As the most commonly used aerogel carrier, SiO2 aerogel has good thermal insulation properties and can generate local hot spots during the reaction, thereby reducing the activation energy of the reaction and improving the catalytic efficiency. At the same time, its excellent light transmittance ensures the effective absorption of light energy by the active components.
[0006] Therefore, the present invention aims to develop a nickel-based catalyst with SiO2 aerogel as a carrier, in order to achieve better catalytic activity in the methane dry reforming reaction and provide a new idea for the reduction of greenhouse gas emissions. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide an aerogel photothermal catalyst in view of the deficiencies of the prior art, in which active nanoparticles are evenly dispersed in the mesoporous channels of the silica aerogel carrier, and the confinement effect of the channel wall effectively inhibits the aggregation of active nanoparticles, thereby significantly reducing the formation of carbon deposits and improving the stability of the catalyst. At the same time, the thermal conductivity of the aerogel itself is extremely low, which can effectively avoid the loss of heat, form local high temperature near the active point, reduce the reaction barrier, and thus promote the methane dry reforming reaction.
[0008] In order to solve the above technical problems, the present invention discloses a method for preparing a nickel-based aerogel catalyst, and the specific steps are as follows:
[0009] S1. Anhydrous ethanol, tetramethoxysilane and dimethylacetamide were mixed uniformly, and then aqueous ammonia was added and mixed uniformly to obtain a sol;
[0010] S2. The sol is sealed in a mold and allowed to stand to obtain a wet gel;
[0011] S3. The wet gel is immersed in a nickel solution, sealed and aged, and then subjected to supercritical extraction drying and calcination to obtain the nickel-based aerogel catalyst.
[0012] Wherein, in step S1, the mass ratio of anhydrous ethanol, tetramethoxysilane, dimethylacetamide and ammonia water is (1-4):1:(0.1-0.4):0.5;
[0013] Preferably, in step S1, the mass ratio of anhydrous ethanol, tetramethoxysilane, dimethylacetamide and ammonia water is 2:1:0.125:0.5.
[0014] Wherein, in step S3, the nickel solution is an alcohol solution of nickel nitrate, and the mass fraction of nickel in the nickel solution is 0.2-5wt%;
[0015] Preferably, in step S3, the mass fraction of nickel in the nickel solution is 0.5 wt %.
[0016] Wherein, in step S3, the mass ratio of the wet gel to the nickel solution is 1:(3-5); the aging process lasts for 4-6 days;
[0017] Preferably, in step S3, the mass ratio of the wet gel to the nickel solution is 1:4; and the aging process lasts for 5 days.
[0018] Wherein, in step S3, the drying conditions of the supercritical extraction equipment are: critical temperature of 45°C, critical pressure of 9-13MPa, supercritical fluid CO2, CO2 flow rate of 22L / h, and drying time of 7-15h;
[0019] Preferably, in step S3, the drying conditions of the supercritical extraction equipment are: critical temperature of 45° C., critical pressure of 10 MPa, supercritical fluid CO2, CO2 flow rate of 22 L / h, and drying time of 13 h.
[0020] Among them, in step S3, the calcination conditions are: introducing a mixed gas of 10% H2 and 90% Ar, with a flow rate of 50 ml / min, adjusted to 20 ml / min after 10 minutes, a heating rate of 10°C / min, and calcining at 700°C for 2 hours.
[0021] Specifically, in some embodiments of the present invention, a nickel-based aerogel catalyst is prepared by the above-mentioned preparation method;
[0022] Wherein, the nickel-based aerogel catalyst uses silicon dioxide as an aerogel carrier, and the loading amount of metal nickel in the nickel-based aerogel catalyst is 0.53-10.48wt%;
[0023] Preferably, the loading amount of metallic nickel in the nickel-based aerogel catalyst is 1.26wt%.
[0024] Specifically, in some embodiments of the present invention, the catalytic reaction activity of the nickel-based aerogel catalyst on a CH4 / CO2 mixed reaction gas under irradiation of a xenon lamp in a fixed bed reactor is evaluated to verify the application prospect of the nickel-based aerogel catalyst in methane dry reforming reaction.
[0025] Beneficial effects: 1) The aerogel catalyst of the present invention has a large average specific surface area and mesopores with an average pore size of 20-40 nm, which can improve the dispersibility of the nickel-based catalyst, increase the contact sites of the reactants, accelerate the transfer of reactants and adsorption to the active sites, thereby improving the catalytic activity of the material.
[0026] 2) The present invention adopts a supercritical drying method in the preparation process, thereby avoiding the problem of porous structure destruction caused by liquid surface tension in the traditional drying process. The complete mesoporous channels confine the nickel nanoparticles, so that the catalyst has good resistance to carbon deposition and sintering, thereby improving the stability of the catalyst.
[0027] 3) The aerogel monolithic catalyst of the present invention has better catalytic performance than the traditional powder catalyst.
[0028] 4) The SiO2 aerogel used in the present invention as a macroscopic carrier of the catalyst has good light transmittance, which is beneficial to improving the utilization rate of light by active metals in the catalytic process. DETAILED DESCRIPTION
[0029] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0030] Example 1: Effect of the ratio of aerogel raw material components on aerogel structure
[0031] (1) Weigh 4 g of tetramethoxysilane, and then weigh the corresponding masses of anhydrous ethanol, dimethylacetamide and ammonia water according to the following mass ratios;
[0032]
[0033] Add half of the weighed anhydrous ethanol, tetramethoxysilane and dimethylacetamide into a 50ml beaker and stir at 200r / min for 5min to obtain solution A; add the remaining half of the anhydrous ethanol and dilute ammonia water (0.16wt%) into a 50ml beaker and stir at 200r / min for 5min to obtain solution B;
[0034] (2) After the two are mixed evenly, solution B is slowly added to solution A. After stirring and hydrolyzing at 200 r / min for 5 min, the sol is transferred into a mold, sealed, and allowed to stand for 1 h to form a wet gel.
[0035] (3) Weigh 1.579 g Ni(NO3)2·6H2O and add it to 30 g anhydrous ethanol, stir evenly until it is completely dissolved, take 7.5 g wet gel and immerse it in it, seal and age for more than 5 days to ensure that the solvent in the wet gel is fully replaced;
[0036] (4) Soak the aged wet gel in an ethanol atmosphere and place it in a supercritical extraction device, slowly introduce air, and adjust the parameters in the drying kettle to 45°C, 10MPa, 22L / h CO2 flow rate, and 13h cycle time;
[0037] (5) The dried aerogel was placed in a tubular furnace, and 10% H2 and Ar were introduced at a flow rate of 50 ml / min. After 10 minutes, the flow rate was adjusted to 20 ml / min, the heating rate was 10°C / min, and the aerogel was calcined and reduced at 700°C for 2 hours to obtain a nickel silica aerogel catalyst.
[0038] In this embodiment, tetramethoxysilane is used as the silicon source of silica aerogel, and dimethylacetamide is used as a drying control agent, which can strengthen the aerogel skeleton and homogenize the aerogel three-dimensional network. Table 1 shows the effect of different group distribution ratios on the aerogel structure. The porosity is obtained by gas adsorption method (BET method); a regular shape sample is selected, its volume v is measured, and the mass m is weighed using a precision balance, and the sample density ρ=m / v is calculated. It can be seen from Table 1 that the larger the mass ratio of the silicon source, the denser the aerogel structure obtained, the greater the density, and the smaller the porosity. At the same time, if the mass ratio of the silicon source is too small, the gel time will be too long, and the aerogel skeleton will be loose and easy to crack and break, so the preferred mass ratio of anhydrous ethanol, tetramethoxysilane, dimethylacetamide and ammonia water is 2:1:0.125:0.5.
[0039] Table 1 Effect of different group ratios on aerogel structure
[0040]
[0041]
[0042] Example 2: Effect of supercritical drying cycle time on aerogel catalyst
[0043] According to Example 1, the mass ratio of anhydrous ethanol, tetramethoxysilane, dimethylacetamide and ammonia water is controlled to be 2:1:0.125:0.5.
[0044] (1) Add 4 g of anhydrous ethanol, 4 g of tetramethoxysilane and 0.5 g of dimethylacetamide into a 50 ml beaker and stir at 200 r / min for 5 min to obtain solution A; add 4 g of anhydrous ethanol and 2 g of dilute ammonia water (0.16 wt%) into a 50 ml beaker and stir at 200 r / min for 5 min to obtain solution B.
[0045] (2) After the two are mixed evenly, solution B is slowly added to solution A. After stirring and hydrolyzing at 200 r / min for 5 min, the sol is transferred into a mold, sealed, and allowed to stand for 1 h to form a wet gel.
[0046] (3) Weigh 1.579 g Ni(NO3)2·6H2O and add it to 30 g anhydrous ethanol, stir evenly until it is completely dissolved, take 7.5 g wet gel and immerse it in it, seal and age for more than 5 days to ensure that the solvent in the wet gel is fully replaced;
[0047] (4) The aged wet gel was immersed in an ethanol atmosphere and placed in a supercritical extraction device, and the air was slowly introduced. The parameters in the drying reactor were adjusted to be a temperature of 45°C, a pressure of 10 MPa, a CO2 flow rate of 22 L / h, and the cycle time was controlled to be 7, 9, 11, 13, and 15 h, respectively;
[0048] (5) The dried aerogel was placed in a tubular furnace, and 10% H2 and Ar were introduced at a flow rate of 50 ml / min. After 10 minutes, the flow rate was adjusted to 20 ml / min, the heating rate was 10°C / min, and the aerogel was calcined and reduced at 700°C for 2 hours to obtain a nickel silica aerogel catalyst.
[0049] The catalytic activity of the catalysts prepared with different drying cycle times was evaluated. The specific evaluation method is as follows:
[0050] 42 mg of aerogel catalyst was weighed and loaded into a fixed bed reactor. H2 was introduced (flow rate of 20 ml / min). After venting for half an hour, the reactor heating program was turned on (heating rate of 10 °C / min). After reaching 700 °C, it was reduced for 1 hour. After naturally cooling to room temperature, a mixed reaction gas of CH4 / CO2 = 1:1 (volume ratio) was introduced (flow rate of 20 ml / min). The exhaust was continued for half an hour. After stabilization, the temperature was raised again (heating rate of 10 °C / min). When the temperature reached 700 °C and stabilized for 5 minutes, the xenon lamp was turned on with a light intensity of 3.7 W / cm 2 After stabilization for another five minutes, the product was measured and detected by gas chromatography online analysis.
[0051] Table 2 shows the catalytic performance test results of catalysts prepared at different drying times. It can be seen from Table 2 that the longer the drying time, the more complete the structure, the larger the specific surface area of the aerogel catalyst, the higher the conversion rate during the catalytic reaction, and the greater the yield. The performance of the drying time of 13h and 15h is similar, indicating that the drying has been thorough and the gel structure is complete. Considering the economy, the drying time of 13h is better.
[0052] Table 2 Catalytic performance test results of catalysts prepared at different drying times
[0053]
[0054] Example 3: Effect of critical pressure of supercritical drying on aerogel catalyst
[0055] (1) Add 4 g of anhydrous ethanol, 4 g of tetramethoxysilane and 0.5 g of dimethylacetamide into a 50 ml beaker and stir at 200 r / min for 5 min to obtain solution A; add 4 g of anhydrous ethanol and 2 g of dilute ammonia water (0.16 wt%) into a 50 ml beaker and stir at 200 r / min for 5 min to obtain solution B.
[0056] (2) After the two are mixed evenly, solution B is slowly added to solution A. After stirring and hydrolyzing at 200 r / min for 5 min, the sol is transferred into a mold, sealed, and allowed to stand for 1 h to form a wet gel.
[0057] (3) Weigh 1.579 g Ni(NO3)2·6H2O and add it to 30 g anhydrous ethanol, stir evenly until it is completely dissolved, take 7.5 g wet gel and immerse it in it, seal and age for more than 5 days to ensure that the solvent in the wet gel is fully replaced;
[0058] (4) Soak the aged wet gel in an ethanol atmosphere and place it in a supercritical extraction device, slowly introduce air, adjust the parameters in the drying kettle to a temperature of 45°C, pressures of 9, 10, 11, 12 and 13 MPa, CO2 flow rate of 22 L / h, and a cycle time of 13 h;
[0059] (5) The dried aerogel was placed in a tubular furnace, and 10% H2 and Ar were introduced at a flow rate of 50 ml / min. After 10 minutes, the flow rate was adjusted to 20 ml / min, the heating rate was 10°C / min, and the aerogel was calcined and reduced at 700°C for 2 hours to obtain a nickel silica aerogel catalyst.
[0060] The performance of catalysts prepared at different critical pressures was tested. Table 3 shows the test results of catalyst performance prepared at different critical pressures. It can be seen from Table 3 that as the critical pressure increases, the skeleton of the aerogel will be partially broken, the conversion rate will decrease during the catalytic reaction, and the performance will deteriorate. When the critical pressure is too low, supercritical carbon dioxide and ethanol will not be completely miscible, the drying will not be thorough, the aerogel structure will be destroyed, and the efficiency will be reduced. In summary, the critical pressure of 10MPa is better.
[0061] Table 3 Performance test results of catalysts prepared at different critical pressures
[0062]
[0063] Example 4: Effect of Ni loading on aerogel catalyst
[0064] (1) Add 4 g of anhydrous ethanol, 4 g of tetramethoxysilane and 0.5 g of dimethylacetamide into a 50 ml beaker and stir at 200 r / min for 5 min to obtain solution A; add 4 g of anhydrous ethanol and 2 g of dilute ammonia water (0.16 wt%) into a 50 ml beaker and stir at 200 r / min for 5 min to obtain solution B;
[0065] (2) After the two are mixed evenly, solution B is slowly added to solution A. After stirring and hydrolyzing at 200 r / min for 5 min, the sol is transferred into a mold, sealed, and allowed to stand for 1 h to form a wet gel.
[0066] (3) Weigh 0.303 g, 0.769 g, 1.579 g, 3.33 g and 10 g Ni(NO3)2·6H2O respectively, add them into 30 g anhydrous ethanol and stir evenly until completely dissolved, take 7.5 g wet gel and immerse it in it, seal and age for more than 5 days to ensure that the solvent in the wet gel is fully replaced;
[0067] (4) Soak the aged wet gel in an ethanol atmosphere and place it in a supercritical extraction device, slowly introduce air, and adjust the parameters in the drying kettle to 45°C, 10MPa, 22L / h CO2 flow rate, and 13h cycle time;
[0068] (5) The dried aerogel was placed in a tubular furnace, and 10% H2 and Ar were introduced at a flow rate of 50 ml / min. After 10 minutes, the flow rate was adjusted to 20 ml / min, the heating rate was 10°C / min, and the aerogel was calcined and reduced at 700°C for 2 hours to obtain a nickel silica aerogel catalyst.
[0069] The effect of different Ni loadings on the performance of aerogel catalysts was tested. Table 4 shows the performance evaluation results of catalysts with different Ni loadings. The Ni loadings were detected by ICP-OES characterization method. It can be seen from Table 4 that the change in catalyst loading significantly affects its activity. The catalytic performance is optimal when the loading is 1.26wt%, and is worst when the loading is the highest. This is mainly because a higher loading will cause the collapse of the aerogel pores, shrinkage of the overall size, or even cracking, thereby reducing the catalytic activity and stability. On the contrary, a lower loading can better maintain the pore structure of the aerogel, maintaining the catalytic activity and stability. The reason why the catalytic activity of a loading of 1.26wt% is better than that of 0.53wt% is that the lower loading reduces the catalyst's ability to absorb light, resulting in a decrease in light energy utilization, and the reaction active sites are also reduced, resulting in a certain degree of decrease in catalytic efficiency.
[0070] Table 4 Performance evaluation results of catalysts with different Ni loadings
[0071]
[0072] Example 5: Stability evaluation of aerogel photothermal catalyst
[0073] (1) Add 4 g of anhydrous ethanol, 4 g of tetramethoxysilane and 0.5 g of dimethylacetamide into a 50 ml beaker and stir at 200 r / min for 5 min to obtain solution A; add 4 g of anhydrous ethanol and 2 g of dilute ammonia water (0.16 wt%) into a 50 ml beaker and stir at 200 r / min for 5 min to obtain solution B;
[0074] (2) After the two are mixed evenly, solution B is slowly added to solution A. After stirring and hydrolyzing at 200 r / min for 5 min, the sol is transferred into a mold, sealed, and allowed to stand for 1 h to form a wet gel.
[0075] (3) Weigh 1.579 g Ni(NO3)2·6H2O and add it to 30 g anhydrous ethanol, stir evenly until it is completely dissolved, take 7.5 g wet gel and immerse it in it, seal and age for more than 5 days to ensure that the solvent in the wet gel is fully replaced;
[0076] (4) Soak the aged wet gel in an ethanol atmosphere and place it in a supercritical extraction device, slowly introduce air, and adjust the parameters in the drying kettle to 45°C, 10MPa, 22L / h CO2 flow rate, and 13h cycle time;
[0077] (5) The dried aerogel was placed in a tubular furnace, and 10% H2 and Ar were introduced at a flow rate of 50 ml / min. After 10 minutes, the flow rate was adjusted to 20 ml / min, the heating rate was 10°C / min, and the aerogel was calcined and reduced at 700°C for 2 hours to obtain a nickel silica aerogel catalyst.
[0078] The stability of the aerogel photothermal catalyst prepared in this example was evaluated. The specific method was as follows: the aerogel catalyst was loaded into a fixed bed reactor, H2 was introduced (flow rate of 20 ml / min), and after exhausting for half an hour, the reactor heating program was turned on (heating rate of 10°C / min), and it was reduced for 1 hour after reaching 700°C; after naturally cooling to room temperature, a mixed reaction gas of CH4 / CO2=1:1 (volume ratio) was introduced (flow rate of 20 ml / min), and exhaust was conducted for half an hour. After stabilization, the temperature was raised again (heating rate of 10°C / min), and when the temperature reached 700°C, it was stabilized for 5 minutes, and the xenon lamp was turned on, and the light intensity was 3.7 W / cm 2 After stabilization for another five minutes, the product was measured and the measurement was continued for 12 hours. The product was detected by gas chromatography online analysis.
[0079] Table 5 shows the stability evaluation results of the catalyst prepared in this example. It can be seen from Table 5 that the conversion rate of the catalyst is almost unchanged after continuous operation for 12 hours, which shows good stability.
[0080] Table 5 Catalyst stability evaluation results of Example 5
[0081]
[0082] Comparative Example 1: Effect of light on the performance of aerogel catalyst
[0083] The preparation of the aerogel photothermal catalyst was the same as in Example 5, except that the xenon lamp was not turned on during the evaluation of the catalytic activity.
[0084] The performance test results of the aerogel photothermal catalysts prepared in Example 5 and Comparative Example 1 are shown in Table 6:
[0085] Table 6 Performance evaluation results of the catalysts of Example 1 and Comparative Example 1
[0086]
[0087] It can be seen from Table 6 that when the reaction temperature of the same catalyst is 700°C, the efficiency of photothermal catalysis in Example 5 is much greater than that of thermal catalysis in Comparative Example 1, and the ratio of H2 / CO is also higher. This shows that the introduction of light energy can reduce the activation energy of the reaction, greatly improve the catalytic efficiency, and inhibit the reverse water-coal reaction, thereby improving the catalytic selectivity. Comparative Example 2: Comparison of the performance of site-exposed catalysts and aerogel catalysts
[0088] The steps for preparing the site-exposed catalyst are as follows:
[0089] (1) Dissolve 124 mg Ni(NO3)2·6H2O in 25 mL deionized water to obtain a Ni precursor salt solution;
[0090] (2) Disperse 500 mg of SiO2 powder in 25 mL of deionized water and sonicate for 15 min;
[0091] (3) adding the solution in step (1) dropwise to the solution in step (2) during rapid stirring;
[0092] (4) After stirring in an oil bath at 80°C until all water is removed, the sample is placed in an oven and dried at 105°C overnight;
[0093] (5) Grinding the dried sample for 10 min, and then placing it in a muffle furnace and heating it to 450 °C at a heating rate of 2 °C / min for calcination for 2 h to obtain a nickel oxide catalyst;
[0094] (6) Finally, the sample was placed in a tubular furnace and heated to 700 °C at a heating rate of 10 °C / min under a hydrogen atmosphere for reduction for 2 h to obtain a site-exposed catalyst.
[0095] The performance of the catalysts prepared in Example 5 and Comparative Example 2 was tested. Table 7 shows the performance evaluation results of the two. It can be seen from Table 7 that both Example 5 and Comparative Example 2 use nickel as the active metal and SiO2 as the carrier. When the carrier is in the form of aerogel, the performance of the catalyst is significantly improved.
[0096] Table 7 Performance evaluation results of the catalysts of Example 5 and Comparative Example 2
[0097]
[0098] The present invention provides a method for preparing a nickel-based aerogel catalyst and an idea for its application. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for preparing a nickel-based aerogel catalyst, characterized in that: The specific steps are as follows: S1. Anhydrous ethanol, tetramethoxysilane and dimethylacetamide were mixed uniformly, and then aqueous ammonia was added and mixed uniformly to obtain a sol; S2. The sol is sealed in a mold and allowed to stand to obtain a wet gel; S3. The wet gel is immersed in a nickel solution, sealed and aged, and then subjected to supercritical extraction drying and calcination to obtain the nickel-based aerogel catalyst.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of anhydrous ethanol, tetramethoxysilane, dimethylacetamide and ammonia water is (1-4):1:(0.1-0.4):0.
5.
3. The preparation method according to claim 1, characterized in that: In step S3, the nickel solution is an alcohol solution of nickel nitrate, and the mass fraction of nickel in the nickel solution is 0.2-5wt%.
4. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of the wet gel to the nickel solution is 1:(3-5); and the sealing aging time is 4-6 days.
5. The preparation method according to claim 1, characterized in that: In step S3, the conditions for supercritical extraction drying are: critical temperature of 45°C, critical pressure of 9-13 MPa, supercritical fluid CO2, CO2 flow rate of 22 L / h, and drying time of 7-15 h.
6. The preparation method according to claim 1, characterized in that: In step S3, the calcination is carried out in a reducing atmosphere, and the conditions are: a mixed gas of 10% H2 and 90% Ar is introduced at a flow rate of 50 ml / min, which is adjusted to 20 ml / min after 10 minutes, a heating rate of 10°C / min, and calcination at 700°C for 2 hours.
7. A nickel-based aerogel catalyst prepared by the preparation method according to any one of claims 1 to 6.
8. The nickel-based aerogel catalyst according to claim 7, characterized in that: The nickel-based aerogel catalyst uses silicon dioxide as an aerogel carrier, and the loading amount of metal nickel in the nickel-based aerogel catalyst is 0.53-10.48 wt%.
9. Use of the nickel-based aerogel catalyst according to claim 7 in a methane dry reforming reaction.
Citation Information
Patent Citations
Preparation method of mesoporous confinement nickel-based methane dry reforming catalyst
CN103586030A
Preparation method of nickel-base methane dry-reforming catalyst of aerogel-like structure
CN105170156A
Method for preparing silica aerogel and self-hydrophobic silica aerogel heat preservation felt pad through one-step technology
CN111039295A
Ni-Ir / SiO2 bimetallic catalyst as well as preparation method and application thereof
CN112973730A
Preparation method of Co3O4-NiO-SiO2 aerogel catalytic material
CN113231066A